The Risks of Digitalization and the Adaptation of Regional Labor Markets in Russia - Stepan Zemtsov; Vera Barinova; Roza Semenova (Foresight and STI Governance, 2019)
The implementation of new automation technologies together with the development of artificial intelligence can free up a significant amount of labor. This sharply increases the risks of digital transformation. At the same time, certain regions and cities differ greatly in their ability to adapt to future changes. In this article, we seek to determine the capabilities of Russian regions to reduce risks and adapt to digital transformation. The literature stipulates that there are several factors able to reduce these risks. First of all, they are associated with retraining, ICT and STEAM-technologies’ development, the promotion of economic activities that are less subject to automation. As a result of econometric calculations, we identified several factors that contribute to the new industries’ development (in our case, ICT development), and, accordingly, increase regional adaptivity. These factors  include diversification, the concentration of human capital, favorable entrepreneurship conditions, the creative potential of residents, and the development of ICT infrastructure. We identified several regions with high social risks and low adaptivity, which are mainly the poorly developed regions of southern Russia, where entrepreneurial risks are high, STEAM specialists are not trained, shadow economy is large. This work contributes policy tools for adaptation to digital transformation.